2011
DOI: 10.1158/0008-5472.can-10-1923
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell 5-Lipoxygenase Activity Promotes Intestinal Polyposis in APCΔ468 Mice

Abstract: Arachidonic acid metabolism has been implicated in colon carcinogenesis, but the role of hematopoietic 5-lipoxygenase (5LO) that may impact tumor immunity in development of colon cancer has not been explored. Here we show that tissue-specific deletion of the 5LO gene in hematopoietic cells profoundly attenuates polyp development in the APC D468 murine model of colon polyposis. In vitro analyses indicated that mast cells in particular utilized 5LO to limit proliferation of intestinal epithelial cells and to mob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 46 publications
2
62
0
1
Order By: Relevance
“…These genetic changes may license the functional changes of MDSC observed during the tumor growth. Although we and others have identified the function of several genes important in the immunosuppressive function of MDSCs (26)(27)(28)(29)(30), many genes still remain unknown. For instance, it is interesting that all neutrophil serine proteases (NSPs), including neutrophil elastase, cathepsin G, and proteinase-3, are increased in Mo-MDSCs, and serpinb1, which is an NSP inhibitor, was increased in both Mo-MDSCs and PMN-MDSCs (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These genetic changes may license the functional changes of MDSC observed during the tumor growth. Although we and others have identified the function of several genes important in the immunosuppressive function of MDSCs (26)(27)(28)(29)(30), many genes still remain unknown. For instance, it is interesting that all neutrophil serine proteases (NSPs), including neutrophil elastase, cathepsin G, and proteinase-3, are increased in Mo-MDSCs, and serpinb1, which is an NSP inhibitor, was increased in both Mo-MDSCs and PMN-MDSCs (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…2C, 2D). In addition, lipocalin 2 (Lcn2), which is an iron-binding protein that promotes tumor metastasis (28,29), and leukotriene A4 hydrolase (Lta4h), which is involved in leukotriene B4-mediated MDSC chemoattraction (30), were also increased in Mo-MDSCs and PMN-MDSCs, respectively, at the late time point. These data suggest that MDSCs are genetically regulated to possess protumor functions as tumors grow.…”
Section: Mo-mdscs and Pmn-mdscs Express Tumor-promoting Genes At Latementioning
confidence: 99%
“…Because mast cells have been described for their ability to mobilize MDSCs at the TME (13,14), we decided first to verify this mast cell capability in our colon cancer model. We performed in vitro migration assays and confirmed that supernatants from IgE/Ag-activated BMMCs induced the migration of both purified PMN-and M-MDSCs, and these had respectively an additive or synergistic effect with CT-26-conditioned culture media-induced migration.…”
Section: Mast Cells Potentiate Monocytic Mdsc-suppressive Properties mentioning
confidence: 99%
“…Protumor mast cells are able to mobilize the infiltration of highly suppressive MDSCs, likely by increasing CCL-2 levels within the tumor lesion, and to induce these cells to produce IL17 that indirectly attract Tregs and enhance their suppressor function (13). Other findings by Cheon and colleagues (14) suggest that in the APCD468 murine model of colon polyposis, mast cells could support and mobilize MDSCs via 5-lipoxygenase activity to drive immune escape with an increase in polyp development. The idea that mast cells can enhance the immunosuppressive function of MDSCs is further supported by recent in vivo data showing that MDSCs depend on mast cells to exert their protumor suppressive function (15,16).…”
Section: Introductionmentioning
confidence: 97%
“…Of note, in 5-LO-competent mice, infiltrating MDSCs also show an increased arginase activity. 5 In a mouse model of melanoma metastasis (through intravenous injection of B16 melanoma cells to recapitulate lung colonization), it has been demonstrated that adoptive transfer of MDSCs induces immunosuppression and increases the average number of lung metastases in wt mice but not in c-Kit Wsh/Wsh . These data suggest that MCs are required to enhance MDSC-mediated immune suppression and tumor escape from immune response, with, in particular, a role attributed to the monocytic-MDSC subset.…”
mentioning
confidence: 99%